2021
DOI: 10.1093/mnras/stab888
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling short-period binaries in the inner VVV bulge

Abstract: Most of our knowledge of the structure of the Milky Way has come from the study of variable stars. Among these variables, mimicking the periodic variation of pulsating stars, are eclipsing binaries. These stars are important in astrophysics because they allow us to directly measure the radii and masses of the components, as well as the distance to the system, thus being useful in studies of Galactic structure alongside pulsating RR Lyrae and Cepheids. Using the distinguishing features of their light curves, on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In passing, we note that the inclusion of RRc variables is crucial to investigate the topology of the instability strip and to address several open problems concerning field and cluster RRLs. However, their inclusion brings forward the thorny problem of short period eclipsing binaries mimicking the luminosity variation typical of RRc variables (Botan et al 2021). To overcome the contamination of eclipsing binaries we devised a new method based on the optical (Gaia, Clementini et al 2019) and mid-infrared (MIR from NEOWISE, Mainzer et al 2011) amplitude ratios.…”
Section: The Rrl Spectroscopic Catalogmentioning
confidence: 99%
“…In passing, we note that the inclusion of RRc variables is crucial to investigate the topology of the instability strip and to address several open problems concerning field and cluster RRLs. However, their inclusion brings forward the thorny problem of short period eclipsing binaries mimicking the luminosity variation typical of RRc variables (Botan et al 2021). To overcome the contamination of eclipsing binaries we devised a new method based on the optical (Gaia, Clementini et al 2019) and mid-infrared (MIR from NEOWISE, Mainzer et al 2011) amplitude ratios.…”
Section: The Rrl Spectroscopic Catalogmentioning
confidence: 99%
“…the VIVACE catalogu (Molnar et al 2021), and previous works on individual Galactic regions (e.g. Molina et al 2019;Medina et al 2021;Alonso-García et al 2021), searches for short-timescale pulsating sources (Bhardwaj et al 2017;Minniti et al 2017) and eclipsing binaries (Botan et al 2021). Contreras Peña et al (2017a, hereafter Paper I) identified 816 variables (Δ𝐾 𝑠 > 1 mag) from the first 4.5 years of the VVV data for the Galactic mid-plane region, including 247 long-term periodic variables (𝑃 > 100 d), among them 65 YSO candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to these surveys, a time-domain survey with high cadence using PRIME will play an important role in providing new insights into the formation history and structure of our galaxy. In addition to aspects of microlensing, the time-domain data by the PRIME microlensing survey will provide useful information in studies of the Galactic structure, through variable stars such as eclipsing binaries, pulsating RR Lyrae, and Cepheids (e.g., Pietrukowicz et al 2020;Botan et al 2021).…”
Section: Inner Galactic Bulge Survey By Primementioning
confidence: 99%